Implikasi Budaya Organisasi Dan Kepemimpinan Terhadap Kinerja Karyawan Pada Bank Bri Karawang - Gian Dirgantara; Sonny Hersona GW (Islamic University of Kalimantan MAB Banjarmasin, 2022)
Employee performance is very important in an organization, because the success of an organization is very dependent on the quality and performance of human resources in the organization. Several aspects of employee performance levels are needed and can be determined at the same time, including organizational culture and leadership capabilities. Several previous studies have shown that the role of organizational culture is very important, and it is very likely that it is motivated by leaders in the organization. Banking is one of the industries with a fairly high employee turnover rate. Therefore, this research was conducted in one of the branches of BRI Bank Karawang branch. The purpose of this study was to examine its effect on employee performance, organizational culture and leadership. The research was conducted at Bank BRI Karawang, with a sample of 70 employees. Data was collected using a questionnaire as a research tool. The analysis technique used is multiple linear regression analysis. The results of the analysis show that organizational culture has a positive effect on employee performance, while leadership has an effect on employee performance. However, the results of the influence of leadership show better results than organizational culture.